DETERMINATION OF SO4β1 FOR YTTRIUM AND THE RARE EARTH ELEMENTS AT I = 0.66 M AND T = 25°C-IMPLICATIONS FOR YREE SOLUTION SPECIATION IN SULFATE-RICH WATERS - Schijf J.; Byrne R.H. (My University, 2004)
We present a complete set of stability constants ( SO 4β 1) for the monosulfato-complexes of yttrium and the rare earth elements (YREE), except Pm, at I = 0.66 m and t = 25°C, where SO 4β 1 = [MSO 4+] × [M 3+] -1[SO 42-] -1 (M ≡ YREE and brackets indicate free ion concentrations on the molal scale). Stability constants were determined by investigating the solubility of BaSO 4 in concentrated aqueous solutions of MCl 3. This is the first complete set to be published in more than 30 years. The resulting SO 4β 1 pattern is very similar in shape to one reported by de Carvalho and Choppin (1967a) ( I = 2 mol/L; t = 25°C) that has been largely ignored. Stability constants vary little between La and Sm, but display a weak maximum at Eu. Between Eu and Lu, SO 4β 1 decreases by 0.2 log units, substantially exceeding the ±0.02 log unit average analytical precision. The stability constant for Y is approximately equal to that for Er. Our SO 4β 1 pattern is consequently distinctly different from the consensus pattern, based on a single data set from 1954, which is essentially flat, with a range of only 0.07 log units between the lowest and highest SO 4β 1 values within the lanthanide series (excluding Y). Values of SO 4β 1 obtained in this work, in conjunction with the ion-pairing model of Millero and Schreiber (1982), allow prediction of SO 4β 1 between 0 and 1 m ionic strength. These results are used to assess both the absolute and relative extent of YREE sulfate complexation in acidic, sulfate-rich waters.